In vitro study of the effect of an essential oil and a delmopinol mouth rinse on dental plaque bacteria - Henrique Soares Luís; Luis Soares Luis; Mário Bernardo (Wolters Kluwer Medknow Publications, 2016)
Context: Mouthrinses are used, by many of our patients, as a complement to daily dental hygiene routine. The use of a toothbrush and an interproximal cleaning method may not be enough to control dental plaque. Essential oils and delmopinol mouth rinses are effective for the prevention of dental caries and gingivitis. To study the effect of an essential oil and a delmopinol mouth rinse on dental plaque bacteria, an in vitro study was developed. Aims: The objective of this study was to determine the antibacterial activity of an essential oil and a delmopinol mouth rinse on Streptococcus mutans, Lactobacilli, and aerobic and anaerobic dental plaque nonspecific bacteria. Design: Samples of human dental plaque were collected from consenting participants and bacteria isolated. Disk-diffusion tests were performed to obtain the minimum concentration of the mouth rinses necessary to inhibit bacterial growth. The ability of the commercial mouth rinses to inhibit bacterial growth was studied in comparison to a positive control (0.2% chlorhexidine) and a negative laboratorial control (sterilized water). Results: The minimum inhibitory concentration was found to be inferior to the commercial essential oils and delmopinol mouth rinses concentrations. Delmopinol and essential oils have significant antibacterial properties shown in vitro only for aerobic bacteria, and for S. mutans, Lactobacillus, and anaerobic bacteria, the results were not statistically significant. Conclusions: Essential oils and chlorhexidine are statistically similar and better than delmopinol for aerobic bacteria growth inhibition. For the other bacteria, essential oils and delmopinol are not statistically promising. Results show that essential oils only may help patients to maintain good oral health as a complement to daily brushing and interproximal cleaning.